Communication Strategy in Public Service Advertisements About Stunting on Social Media - Rusdin, Febi Ramadhani; Rahmat, Felisianus Novandri; Nofiasari, Wida (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Stunting is one of the serious public health issues that is prevalent in Indonesia. Stunting can have adverse effects on the physical and mental growth and development of children, as well as disrupt their future quality of life. Preventing stunting is a goal of Sustainable Development Stage-2, which aims to eliminate hunger and all forms of malnutrition. Social media can be an effective platform for creating public service advertisements. Therefore, a social media advertising campaign is necessary to raise awareness among the public about the dangers of stunting and its prevention, given the high usage of social media today. This research aims to identify effective communication strategies in a public service advertising campaign about stunting on the social media platform Instagram, targeting the right audience. The results of this research will provide a better understanding of effective communication strategies in a public service advertising campaign about stunting on social media for the appropriate target audience. Data analysis indicates that content with an educational narrative receives special attention from the audience, as seen in the number of likes and positive comment interactions from the followers of the Instagram account.